SIS focal plane imaging array for 350 GHz - Leech, J; Withington, S; Yassin, G (IEEE, 1999)
Astronomical interest in millimetre and submillimetre wavelengths (f = 300 GHz to 1 THz) has fuelled the development of low noise high sensitivity detectors for these wavelengths. HARP (Heterodyne Array Receiver Project) will be a 16 element focal plane imaging array of heterodyne detectors for the 850 micron (325 - 375 GHz) band. Each element will consist of a mixer employing an SIS (superconductor - insulator - superconductor) tunnel junction as the non linear device. When attached to the James Clerk Maxwell Telescope in Hawaii the array will offer greatly improved mapping speeds of extended objects complementing existing bolometer detectors and planned millimetre wave aperture synthesis telescopes. This presentation will examine aspects of the SIS device physics, quasi-optics, and electromagnetic design for the HARP imaging array. Original results from computer modelling and experiments on a prototype mixer will be presented.